Plan de mercadeo, para determinar la aceptación de un nuevo servicio a domicilio de combos para celebraciones temáticas en la especialización de pastelería de la empresa martina golosina ubicada en la ciudad de Ambato - Viteri Fiallos, Verónica de los Ángeles (2016)
The cakes and pastries market in Ecuador is competitive and has several bidders that meet consumers maintaining traditional standards The development of this marketing plan in the city of Ambato arises from the need observed through social networks and consumer suggestions, so the idea - initiative to introduce a new service of combos for thematic celebrations that includes delivery service to the address that the consumer needs, all of this is focus in the pastry specialization, which includes a personalized cake and two dozen appetizers, helps to meet the needs and expectations of consumers when celebrating an event with a product according to their needs, delivered at your home for comfort and safety. The proposal measures the acceptance of innovative services and products in the city of Ambato and determines the production volume to generate an attractive, reliable, formal and structured business, through techniques of primary research, applicable in this service because it is new in the city.